2D graphdiyne loading ruthenium atoms for high efficiency water splitting. (June 2020) - Yu, Huidi; Hui, Lan; Xue, Yurui; Liu, Yuxin; Fang, Yan; Xing, Chengyu; Zhang, Chao; Zhang, Danyan; Chen, Xi; Du, Yuncheng; Wang, Zhongqiang; Gao, Yang; et al.
Abstract: The theoretical simulation indicates that the strong coupling between the Ru atoms and neighboring C atoms in GDY makes the Ru to be a unique electron-mediating-vehicle (EMV) for fast reversible redox-switching endowing the catalyst with excellent catalytic performances. Our experimental study is fully in accordance with the theoretical simulation, which shows that the high-activity and ultra-high selectivity of the Ru atomic catalyst. For example, Ru/GDY can deliver 10 mA cm −2 at a low overpotential of 44 mV and exhibits a very small Tafel slope of 30 mV dec −1, comparable to commercial Pt/C, in hydrogen evolution reaction (HER) in acidic conditions. We also found that Ru/GDY has higher catalytic activity and stability for oxygen evolution reaction (OER) than RuO2 in 0.5 M H2 SO4 solutions. Graphical abstract: Image 1 Highlights: Atomic catalysts consisting of GDY and isolated Ru atoms were synthesized for efficient water splitting in acidic media. The determined electron and chemical structure of the catalyst brings a unique electron-mediating-vehicle (EMV) mechanism. Ru/GDY exhibits higher mass activity and turnover frequency than commercial Pt/C and RuO2 in HER and OER, respectively.